2019
DOI: 10.1007/s10643-019-00976-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Preschool Educators’ Implementation of Computer Programming in Their Teaching Practice

Abstract: Modern preschool education is seen as an essential foundation for nurturing children’s digital literacy. Early childhood education environments have witnessed increased emphasis on integrating programming activities in combination with digital tablets. However, little is known about how preschool teachers implement programming as part of pedagogical strategies during practice. In Sweden, although there is a mandate to develop children’s understanding of the digital world, programming is not formally mentioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
(34 reference statements)
1
23
0
7
Order By: Relevance
“…In addition, the majority have a positive attitude towards the integration of computational thinking at all levels of education through STEM activities and interdisciplinary approaches. In addition, several studies have shown that there is a lack of training in CT issues by teachers and therefore not possible to use it in teaching practice [ 25 , 26 , 27 , 28 ]. Finally, research on what is considered CT in a school lesson, showed that various attempts are made by teachers, who realize how important it is to cultivate computational thinking in students for their future development, but themselves (teachers) have not received any comprehensive training on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the majority have a positive attitude towards the integration of computational thinking at all levels of education through STEM activities and interdisciplinary approaches. In addition, several studies have shown that there is a lack of training in CT issues by teachers and therefore not possible to use it in teaching practice [ 25 , 26 , 27 , 28 ]. Finally, research on what is considered CT in a school lesson, showed that various attempts are made by teachers, who realize how important it is to cultivate computational thinking in students for their future development, but themselves (teachers) have not received any comprehensive training on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, one study (i.e., Esteve-Mon et al, 2019) reported that teacher trainers could introduce robotics as an initiation and unplugged activity, since their implementation also revealed positive learning outcomes, while another study (i.e., Miller et al, 2018) used unplugged robotics and reported an increased interest toward engineering. Seven studies (i.e., Otterborn et al, 2019) considered using unplugged approaches in line with plugged approaches and the general conclusion was that the two approaches could be used in combination so as to complement each other. One study (i.e., Gomes et al, 2018) was in favor of this hybrid approach, while another reported “no difference between the two groups in their mastering of programming concepts, the unplugged first group demonstrated more self-efficacy, and that they use a wider vocabulary of Scratch blocks” (Hermans & Aivaloglou, 2017, p. 50).…”
Section: Resultsmentioning
confidence: 99%
“…Many preschool teachers and support staff are unaware of or are untrained in adapting pedagogical approaches that can support computational thinking (Manches & Plowman, 2017). Furthermore, government guidelines for preschool digital technology are very vague or non-existent and it would be helpful for staff if more specific guidelines, such as those used in Swedish preschools, are promoted (Otterborn et al, 2020). The findings from this study suggests play-based, pedagogic practices can be used with children as young as 2 years to learn many of the basic concepts involved in computational thinking skills.…”
Section: Implications and Limitationsmentioning
confidence: 99%